2016
DOI: 10.1111/famp.12237
|View full text |Cite
|
Sign up to set email alerts
|

Family‐Focused Therapy for Bipolar Disorder: Reflections on 30 Years of Research

Abstract: Family-focused therapy (FFT) is an evidence-based intervention for adults and children with bipolar disorder (BD) and their caregivers, usually given in conjunction with pharmacotherapy after an illness episode. The treatment consists of conjoint sessions of psychoeducation regarding bipolar illness, communication enhancement training, and problem-solving skills training. This paper summarizes over 30 years of research on FFT and family processes in BD. Across eight randomized controlled trials with adults and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(109 citation statements)
references
References 56 publications
5
103
0
1
Order By: Relevance
“…Given that the original creation of FFT targeted factors related to depression, it may have specific antidepressant activity, which is also suggested by reduced depression relapse in maintenance studies. For relapse prevention, four significant RCTs of varying sizes have been conducted, delivered to a mixed audience of young adults and adolescents 95. In these studies, FFT demonstrated efficacy in reducing recurrence of new episodes of depression, but not mania.…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…Given that the original creation of FFT targeted factors related to depression, it may have specific antidepressant activity, which is also suggested by reduced depression relapse in maintenance studies. For relapse prevention, four significant RCTs of varying sizes have been conducted, delivered to a mixed audience of young adults and adolescents 95. In these studies, FFT demonstrated efficacy in reducing recurrence of new episodes of depression, but not mania.…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…Bipolar disorder typically first occurs in late adolescence or early adulthood and its course, even when treated with mood‐stabilizing medication, is significantly affected by stressful life events and family circumstances on the one hand, and family support on the other. The high frequency of relapses among young people with bipolar disorder, and the observation that relapse may be associated with high levels of parental expressed emotion, provides the rationale for the development of relapse prevention interventions (Miklowitz and Chung, ). Psychoeducational family therapy aims to prevent relapses by reducing family stress (including parental expressed emotion) and enhancing family support for youngsters with bipolar disorder who are concurrently taking mood‐stabilizing medication (Miklowitz, ).…”
Section: Emotional Problemsmentioning
confidence: 99%
“…Four randomized trials have found that FFT and pharmacotherapy are more effective than brief psychoeducation or individual supportive therapy and pharmacotherapy in reducing symptom severity and delaying recurrences among bipolar adults (Miklowitz and Chung, 2016). The empirical record of FFT-A is less certain in adolescents with BD, with one study showing significant reductions in depressive symptoms among adolescents who received FFT-A compared to EC (Miklowitz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%